(untitled) (Al-Academy, 2025)
Islamic art decorations are a fertile source of art and science. Islamic art has touched on several fields of applied arts such as pottery, ceramics, glass, metals, textiles, and wood. Museums play a role in highlighting the heritage of Islamic art in various artistic styles, which can be highlighted in the educational process in universities as well as helping artists understand various Islamic artworks. This research aims to identify the section dedicated to Islamic arts at the Louvre Museum in Paris (France) in October 2022. The research followed the descriptive analytical approach using various tools to collect information, namely field visits, observation cards, photography, video clips, illustrations, the use of technology tools and artificial intelligence. The most important results resulted in analyzing nine works of art pieces with different techniques from Islamic arts and documenting them with digital images and analyzing them using modern technologies, which helps the researcher classify the artwork in terms of the style of the Islamic era, the type of artwork, the structural and decorative design, the type of decoration, the type of material or technique used, its different colors, the city to which it belongs and the year if any.